Iyabelale as an Accompaniment to Magical Sleeping for Children in the Bugis Ethnic Groups of South Sulawesi - Manggau, Arifin; Jayadi, Karta (The Journal of Educational Development, 2018)
Lyabelale is a lullaby for children in Bugis community and is an activity that has been integrated into the community as a tradition to put children to bed. Lyabelale has a magical function for Bugis community in South Sulawesi because it contains cultural values in their life. For the Bugis ethnic groups, Lyabelale is a child's lullaby that serves as a means of magical ritual in the supporting community. This study aims to examine the magical rituals contained in Lyabelale. This research employed a qualitative method based on an interdisciplinary approach. The study was conducted in three areas where the people were from the Bugis, Bone, Soppeng, and Wajo ethnic groups in South Sulawesi. The results of this study indicate the following. Lyabelale consists of three elements of a magical ritual, namely (1) as a prayer consisting of a) an appeal to God Almighty that the child will be happy and successful in his/her life; b) a hope that the child is filial; c) mother's longing for the family member who is away from home; (2) as a treatment or therapeutic to reduce pain suffered by the child during his/her illness and to relieve the mother/grandmother’s longing for the member of the family who is away from home; (3) as a rejection of evil spirits that can disturb the child in doing his/her activities.